Análisis del cambio de temperatura en Bogotá D.C., durante los últimos 20 años - Romero Rojas, Jairo Alberto; Dávila Ramírez, Marla Alessandra (Universidad Escuela Colombiana de Ingeniería Julio Garavito, 2014)
En este artículo se presenta un análisis de la variación de las temperaturas máximas, medianas y mínimas mensuales de seis estaciones ubicadas en la ciudad de Bogotá, D.C., durante los periodos 1993 - 2002 y 2003 - 2012

This article presents an analysis of the variation in maximum, mean and minimum monthly temperatures in six stations located in Bogotá D.C., durint the 1993 - 2002 and 2003 - 2012 periods.
Temperature change in Bogotá, D.C., last 20 years
Keywords: Cambios climáticos; Climatic changes; Bogotá (Colombia) - Clima; Bogotá (Colombia) - Climate; Temperatura - Variaciones estacionales; Temperature - Seasonal variations; Cambio climático; Temperatura ambiente; Variación de temperatura; Climate change; Ambient temperature; Temperature variation